Physical and dosimetric characteristics of radiophotoluminescent glass from two-photon excitation microscopy. (January 2021) - Kurobori, Toshio; Kada, Wataru; Yanagida, Yuka; Koguchi, Yasuhiro; Nanto, Hidehito
Abstract: We investigate the physical and dosimetric characteristics of Ag-activated phosphate glass exposed to proton beams with various energies. We present time-resolved blue and orange radiophotoluminescent (RPL) spectra and examine the dependence of the peak wavelengths and RPL area intensities on gate time. Moreover, we consider various micro-scale 3D patterns written on Ag-activated glass by a focused proton beam and evaluate their orange and blue RPL axial-profiles using two-photon excitation microscopy. Finally, we discuss the remarkable broadening of the Bragg curve observed in Ag-activated glass and argue that it should be attributed to the saturation effect and/or non-linearity effect from the viewpoint of the relation between the dose delivered and the signal. Highlights: Time-resolved RPL spectra in Ag-activated glass are examined. Micro-scale patterns written by proton beams are studied by two-photon confocal microscopy. Bragg curves of Ag-activated glass and LiF irradiated with protons are compared. Remarkable broadening of the Bragg curve is due to saturation and/or non-linearity effects.